Cervico-oculo-acoustic (Wildervanck) syndrome: clinicoradiological findings - Rihani, Farouk Bassam (BMJ Publishing Group, 2013)
We describe a girl presented with facial asymmetry and oral mucosal cleft and with further investigations other anomalies were found including hearing loss, Duane syndrome, Klippel-Feil anomaly, Chiari malformation and accessory bone mass in mandibular ramus leading to the clinical diagnosis of cervico-oculo-acoustic (Wildervanck) syndrome (COAS). The patient underwent surgical occipital decompression by preforming suboccipital craniectomy and C1 posterior laminectomy to relieve the cerebellar tonsillar herniation. Surgical removal of mandibular bony mass was done and the patient is now under orthodontic treatment to correct facial asymmetry and malocclusion.